If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 = 2x + 5 Reorder the terms: 1 + 6x = 2x + 5 Reorder the terms: 1 + 6x = 5 + 2x Solving 1 + 6x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 6x + -2x = 5 + 2x + -2x Combine like terms: 6x + -2x = 4x 1 + 4x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 4x = 5 + 0 1 + 4x = 5 Add '-1' to each side of the equation. 1 + -1 + 4x = 5 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 5 + -1 4x = 5 + -1 Combine like terms: 5 + -1 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| 0=-x^2-19x-18 | | 50-18=4(x-3) | | 7-21g/7= | | 14x-262=5x-10 | | -(3-3a)=3(a-11) | | x=w^2-v^2 | | 5x^3-30x^2+25x= | | x^3-9x^2+22x-10=0 | | 14-8x=170-36x | | 0=6x^2+24x+2 | | 15c(2c-5)= | | -2(7+5b)+3(2b-3)= | | 2x+x-11+-7x=15 | | -136-8x=170-36x | | G(x)=-x^2-19x-18 | | -12m+8=-13m | | 19=7m+5(3-m) | | 2x-45=6 | | w^2=x+v^2 | | 7(6x+2)= | | x^2-45=20 | | (6c-5)+8(3c+4)= | | 12(3x+6)= | | -2(-2)(-3)(-4)-5= | | 6g=24-2(3+3g) | | 313+n=400 | | 5(h-2)-(3-2h)= | | 7=8x-5y | | 2(4x+9)= | | 2x+11=52-3x | | 4f*2+3f*(-2)= | | -13x+1=-90 |